Three non-phenolic diarylheptanoids with anti-inflammatory activity from Curcuma xanthorrhiza - P. Claeson (2018)
Bioassay-guided fractionation of a hexane extract of the rhizomes of Curcuma xanthorrhiza Roxb. (Zingiberaceae) led to the isolation of three non-phenolic diarylheptanoids, identified mainly by high-field 1H-NMR as trans-trans-1,7-diphenyl-1,3-heptadien-4-one (alnustone), trans-1,7-diphenyl-1-hepten-5-ol, and trans,trans-1,7-diphenyl-1,3-heptadien-5-ol. The latter is reported for the first time as a plant constituent. Germacrone, curzerenone, and cinnamaldehyde were also isolated and identified. The three diarylheptanoids all exerted significant anti-inflammatory activity in the assay of carrageenin-induced hind paw edema in rats.